LI-FI BASED BLIND INDOOR NAVIGATION SYSTEM - Jude, Dr.P.Sebastian Vindro; R, Harrini; P, Khreethi; mathumitha V , krishnalakshmi A (The journal of contemporary issues in business and government, 2021)
LIGHT FIDELITY is popularly known as Li-Fi. Li-ﬁ that is based on the visible light spectrum is being designed. This project uses a 12 V LED and a solar panel to transmit and receive data respectively. Li-ﬁ can be compared with the existing wireless technology i.e. Wi-Fi in terms of speed and security which the former provides better. The aim of this project is to support visually impaired people who travel indoors.This project mainly deals with the transmission of audio, automatic switching of fan and also obstacle detection using a setup of PIC microcontrollers, 12 V LED, Ultrasonic sensor and Solar Panel. The 16*2 LCD Display is used to monitor about the status of the data.